Efficiency of Productive Zakat Distribution in Increasing the Prosperity of Mustahik in Amil Zakat, Infaq, and Sadaqah Muhammadiyah Institutions in South Sumatra Province - Muhammad Jauhari; Afta Kharisma Wijaya (Jurnal I-Philanthropy, 2023)
Zakat, according to Islam, is an obligation that must be carried out by every Muslim. It acts as a tool given by Islam to eradicate poverty by making the rich aware of their social responsibility. There are two types of zakat distribution in Indonesia: consumptive distribution and productive distribution. However, the distribution of zakat is still predominantly dominated by consumptive zakat. The purpose of this research is to investigate how productive zakat can be distributed at LAZISMU South Sumatra and evaluate the success of distributing productive zakat funds to mustahik (those eligible to receive zakat) status. The data collection method used in this thesis research is qualitative. The primary and secondary data sources are utilized, and data is collected through interviews and documentation. Currently, in the distribution of productive zakat, LAZISMU still employs a grant contract, whereby productive zakat funds given to mustahik are provided free of charge. They also use a Qardhul Hasan contract. However, the implications of productive zakat funds for mustahik status have not fully transformed mustahik into muzaki (those who give zakat). Instead, the new mustahik status indicates their ability to transition into muktafi (people who can meet their own needs) and munfiq (people who spend infaq).